Device of biological charcoal preparation haydite of mud pyrolysis - YU CHENG; WANG YIN; YU GUANGWEI (2016)
The utility model discloses a device of biological charcoal preparation haydite of mud pyrolysis, including quantitative feeder, with water installation, humidifying device, shaping prilling granulator, drying device, the medium temperature device of burn -ining, high temperature sintering device and cooling device. The device utilize the biological charcoal of mud pyrolysis preparation haydite, realize the large -scale use of the biological charcoal of mud pyrolysis, realize further high -efficient solidification of heavy metal and passivation in the biological charcoal of mud pyrolysis simultaneously, avoided the biological charcoal of mud pyrolysis to pollute in the accumulation of the latent heavy metal of land use in -process, be particularly useful for the utilization of the mud pyrolysis charcoal that heavy metal content exceeds standard. The device, the equipment investment is few, and is with low costs, has good economic benefits and environmental benefit. 本实用新型公开了种污泥热解生物炭制备陶粒的装置，包括定量给料装置、加水装置、调湿装置、成